Taxation smuggling: the regulatory contribution and how to pass a tax as if it were a contribution - Bullard González, Alfred (2015)
What is the logic of the State for the creation of contributions? When is a contribution denatured and becomes, in effect, a tax? What is the purpose of the existence of a regulatory contribution to different regulatory and oversight entities?Regarding the aforementioned regulatory contribution case, in the present article the authors criticize the fact that the State has created contributions that, in reality, are not contributions that, in reality, are not.